PENYUSUNAN PAKET WISATA KELUARGA DI KABUPATEN TANAH DATAR - Ulfikri, Aulia; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research focuses on developing structured family tourism packages in Tanah Datar Regency, West Sumatra. The study aims to create tourism packages that incorporate essential elements, including accessibility, amenities, attractions, and supporting institutions, to provide a safe, educational, and memorable experience for all family members. The research employs a descriptive qualitative method, collecting data through field observations, in-depth interviews with relevant stakeholders, and document analysis of local tourism publications and records. Accessibility emerges as a key component in developing these packages, with a thorough examination of infrastructure, transportation, and access routes to tourist destinations in Tanah Datar. The findings indicate that integrated family tourism packages, which combine cultural and natural attractions while providing adequate amenities and accessibility, can be an appealing choice for family travelers. These packages not only have the potential to increase tourist arrivals but also positively impact the local economy by creating business opportunities for the surrounding community. Additionally, they serve as a medium for cultural preservation, involving families in activities that introduce Minangkabau traditions to younger generations. By designing educational and interactive tourism packages, this research contributes to efforts in preserving local culture while enhancing the welfare of the Tanah Datar community through the tourism sector. Keywords: Family Tourism Package, Accessibility, Attractions, Amenities, Cultural Preservation, Educational Tourism, Local Economy